Gross incomes in the Belgian SILC dataset: An analysis by means of EUROMOD - André Decoster; Dieter Vandelannoote; Toon Vanheukelom; Gerlinde Verbist (University of Essex, Institute for Social and Economic Research (ISER), 2014)
Income aggregates and poverty and inequality measures tend to show important differences when calculated either with disposable income reported in SILC data, or with the same income concept calculated on the basis of the microsimulation model EUROMOD, which starts from gross incomes in SILC. This is one of the reasons why gross income data in SILC are often regarded with some suspicion. In this paper we try to shed light on this question by 1) comparing gross incomes in SILC with gross incomes reported on the fiscal form for the same individuals; 2) testing a re-calibration of gross incomes proposed by Immervoll and O'Donoghue (2001), to make them consistent with reported net incomes. We find that on average fiscally reported gross incomes exceed gross incomes in the survey. It is not clear however, whether the method of constructing updated gross incomes through an iterative method using the observed net incomes and withholding tax rules, is a genuine improvement upon the reported gross income distribution.
Keywords: C81; R20; 330; household income; administrative data; survey data; microsimulation model